Urban stakeholder analysis for food waste prevention and reduction in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Bandara, A.; Bucatariu, C.; Reitemeier, M.; Drechsel, Pay (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Food waste is a growing concern in Sri Lanka’s urban areas, with local authorities struggling to manage rising volumes from households, markets, restaurants, and institutions. A multi-city assessment across 10 municipalities revealed that despite various actors being involved government agencies, private waste collectors, NGOs coordination remains weak due to fragmented mandates and poor enforcement. Municipalities like Colombo and Kaduwela generate particularly high levels of food waste, especially from public markets. Some cities, including Negombo and Kaduwela, redirect waste to pig farms informally, but most lack structured redistribution systems or legal backing for food recovery. Composting and private-sector collection services exist but are limited by operational challenges. National ministries oversee food production, safety, and waste separately, creating overlap and gaps in implementation at the local level. Civil society initiatives, including food donation and awareness programs, are emerging, but remain small-scale. Without a unified framework, food waste prevention efforts remain piecemeal. The analysis calls for clearer institutional roles, cross-sector collaboration, and the formalization of redistribution channels. Strengthening governance and stakeholder alignment is essential to reducing food loss and achieving circular economy and SDG 12.3 targets in urban Sri Lanka.